Investigation of electric discharge machining parameters to minimize surface roughness - Sarosh, M.; Jahanzaib, Mirza; Mumtaz, J.; Sarfraz, Shoaib (Pakistan Association for the Advancement of Science, 2016)
Surface roughness during electrical discharge machining (EDM) was determined, in which material is removed by thermo-electric process due to the occurrence of successive discharge between workpiece and electrode. Box-Behnken design (BBD) involving four parameters discharge current (I), Pulse ON time (PON), Pulse OFF time (POFF) and Gap voltage, with three levels was employed to minimize the surface roughness. Other parameters such as Servo speed, Polarity and Die-electric pressure were kept constant throughout the machining. A copper electrode tool was used to machine the holes in AISI 1045 steel work piece. Mathematical models were developed using Response Surface Methodology (RSM), while Analysis of variance (ANOVA) was used to observe individual effect, interaction between parameters, and to check validity of models. Results revealed that pulse on time and discharge current were two main significant parameters that statistically affected surface roughness.
Keywords: ANOVA; Electric Discharge Machining; Process Parameters; Response Surface Methodology